Issues, Challenges, and solutions to improve customer satisfaction of Kedah Public Library - Taib, Che Azlan (2017)
There are several types of library such as academic library, corporate library, government library, private library, school library, special library and public library. A public library is a library that is open to the public and generally funded by taxes of the municipal, state or federal level (New World Encyclopedia, 2015). The New World Encyclopedia also addressed that public library typically is lending library, allowing users to borrow books and other materials. It also has a non-circulating reference collection, and usually focuses on popular material such as fiction and movies, as well as educational and nonfiction materials of interest to the general public. Standing as a public library, Perbadanan Perpustakaan Awam Kedah or Kedah Public Library (PPAK) is a part of the largest network of community organizations that are committed to improving the life outcomes for communities. PPAK received the mandate from the state government to serve the general information for public needs, as well as the mandate to serve a specific user such as school, higher education institution, researchers, and State Assembly.Therefore, PPAK reflects the socio-economic and educational status of the country and the society it is located (Perbadanan Perpustakaan Awam Kedah (PPAK), 2017).Thus, the significant attributes of PPAK is their ability to support a broad mission that can appeal to communities.Public libraries are in the perfect place to support connected learning because they are built on a solid foundation of choice—in libraries, communities have been able to choose what they want to read, explore, or participate in.A contemporary library must support four goals: experience, empowerment, involvement, and innovation (State Library Victoria, 2017).